2023
DOI: 10.3390/pathogens12010096
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Weizmannia coagulans Strain SANK70258 Ameliorates Coccidial Symptoms and Improves Intestinal Barrier Functions of Broilers by Modulating the Intestinal Immunity and the Gut Microbiota

Abstract: To determine the mechanisms by which Weizmannia coagulans SANK70258 (WC) supplementation improved growth performance and coccidial symptoms, we assessed the gene expressions and the microbiota compositions in the small intestinal tissues and digestas of coccidium-infected broilers previously given WC or lasalocid-A sodium (AM). WC supplementation significantly upregulated the gene expressions related to intestinal immunity and barrier functions, such as IL17A, IL17F, IL10, cathelicidin-2 and pIgR. Body weights… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…A study of a different strain has shown that ingestion of H. coagulans increases NK cell activity ( 20 ). In addition, the enhancement of intestinal immune function by HC via modification of the intestinal microbiota is reported to contribute to the acquisition of resistance to infection by pathogenic protozoa in livestock and ameliorate weight loss caused by infection ( 21 , 22 ). Several reports have suggested that HC may have immunostimulatory properties; however, few reports have examined the detailed effectiveness of HC on human immune function and its mechanism of action.…”
Section: Introductionmentioning
confidence: 99%
“…A study of a different strain has shown that ingestion of H. coagulans increases NK cell activity ( 20 ). In addition, the enhancement of intestinal immune function by HC via modification of the intestinal microbiota is reported to contribute to the acquisition of resistance to infection by pathogenic protozoa in livestock and ameliorate weight loss caused by infection ( 21 , 22 ). Several reports have suggested that HC may have immunostimulatory properties; however, few reports have examined the detailed effectiveness of HC on human immune function and its mechanism of action.…”
Section: Introductionmentioning
confidence: 99%
“…Bacillus coagulans SANK70258 (B. coagulans SANK70258), also termed Weizmannia coagulans SANK70258, is a lactic acid bacterium used as probiotics for livestock animals and humans. Oral administration of B. coagulans SANK70258 effectively promotes the growth of broiler chickens with conferring the protection ability against Coccidia infection [2,3] and modulates the composition of SCFAs in the intestine [4]. A study using a model culture system of human colonic microbiota revealed that B. coagulans SANK70258 increased the concentration of butyrate and number of Lachnospiraceae bacteria in the intestine and reduced colonic Enterobacteriaceae species [5].…”
Section: Introductionmentioning
confidence: 99%
“…A study of a different strain has shown that ingestion of H. coagulans increases NK cell activity (20). In addition, the enhancement of intestinal immune function by HC via modification of the intestinal microbiota is reported to contribute to the acquisition of resistance to infection by pathogenic protozoa in livestock and ameliorate weight loss caused by infection (21,22). Several reports have suggested that HC may have immunostimulatory properties; however, few reports have examined the detailed effectiveness of HC on human immune function and its mechanism of action.…”
Section: Introductionmentioning
confidence: 99%